The Role of Islamic Religious Education Teachers in Developing Creativity and Innovation in Learning Methods at State Senior High School 9 Pulung Kencana - Pertiwi, Ajeng Amanda; Aziz Q, Ikhwan; Irhamudin, Irhamudin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Islamic Religious Education (PAI) plays a strategic role in developing students' creativity and innovation to face the challenges of modern life while still prioritizing Islamic values. This research aims to explore the role of PAI teachers in encouraging the development of student creativity and innovation, as well as identifying learning challenges and solutions at SMP Negeri 9 Pulung Kencana. This research uses a descriptive qualitative approach with data collection methods through observation, interviews, and documentation, which are analyzed using an interactive model (data collection, data reduction, data presentation, and drawing conclusions). The results of the research show that PAI teachers have a central role as facilitators, motivators, and inspirers in learning that supports the development of student creativity. The use of technology-based learning methods, project approaches, and digital media helps students think critically and creatively. Teachers also create interactive learning environments that allow students to explore, discuss and collaborate. PAI school principals and teachers emphasize the importance of teacher training and learning approaches that are relevant to current developments to encourage students to learn actively and creatively.